Persistent CD8+ T cell-driven immune dysregulation despite normalized CD4+ T cell recovery in ART-treated people living with HIV - Hu, Yiyao; Ge, Lingyun; He, Yun; Li, Xiaorui; Luo, Yinsong; Wu, Hui; He, Jiayi; Zhang, Chao; Liu, Jiaye (Frontiers in Immunology, 2026)
BackgroundDespite successful antiretroviral therapy (ART) that restores CD4+ T cell counts and reduces HIV viral loads to undetectable levels, a substantial proportion of people living with HIV (PLWH) exhibit persistent CD4/CD8 ratio inversion. This abnormal ratio is primarily driven by sustained CD8+ T cell expansion and reflects a state of chronic immune dysregulation and incomplete immune recovery. However, cellular and molecular mechanisms underlying this discordant immune state remain poorly understood.MethodsWe analyzed longitudinal data of 5,416 ART-treated PLWH from Shenzhen Third People’s Hospital, identifying distinct CD8+ T cell trajectory groups using group-based trajectory modeling. We compared those with chronic stable activation (CSA group) versus those with immune modulation recovery (IMR group) using CyTOF-based immunophenotyping, bulk RNA sequencing, and plasma biomarker profiling.ResultsBoth IMR and CSA groups achieved CD4+ T cell recovery, but CSA group exhibited persistently elevated CD8+ T cells and inverted CD4/CD8 ratios. The CSA group displayed a marked expansion of senescent and activated CD8+ T cell subsets and diminished regulatory T cells, characterized by decreased expression of CD196, CD95, and CD27. Bulk RNA sequencing revealed upregulation of interferon-stimulated genes, chemokine signaling pathways and pro-inflammatory transcriptional programs. Consistently, systemic levels of key inflammatory mediators, including IP-10, MCP-1, and soluble CD163, were significantly elevated in the CSA group.ConclusionsPersistent CD8+ T cell activation reflects a distinct immunological state marked by CD4/CD8 ratio inversion, cell senescence, exhaustion, and systemic inflammation. This immune profile may help identify individuals who warrant closer immunological monitoring for non-AIDS complications and may inform future studies aimed at modulating CD8+ T cell-driven immune dysregulation to improve long-term immune restoration.